Alan Cobley (ed.), From Cattle-herding to Editor’s Chair: The Unfinished Autobiography and Writings of Richard Victor Selope Thema (Historia, 2021)
The Van Riebeeck Society (VRS) plays a critical role by making primary sources of history available to the public. Established in August 1918, the society was founded “to print or reprint for distribution among the members, and for sale to the public, rare and valuable books, pamphlets and documents relating to the history of Southern Africa”. The publication of Richard Victor Selope Thema’s (1886–1955) autobiography and writings is another milestone for the society. According to Professor Howard Phillips, the chair of the VRS, the publication of Thema’s writings is “a companion piece to the volume published by the VRS in 2012, A.B. Xuma: Autobiography and Selected Works” (p iv) edited by Peter Limb. Dr Xuma (1893– 1962) was not only a contemporary of Thema, but like Thema, he was also an author of note.
Keywords: Van Riebeeck Society (VRS; 1918; Victor Selope Thema; religion; Christian; South African War